Environmental perceptions on entrepreneurial thinking in the wine industry. Issue 1 (2nd January 2019) - Gilinsky, Armand; Eyler, Robert; Newton, Sandra; Downing, James A.
ABSTRACT: The US wine industry is a well-studied industry with little research observing small business perceptions of entrepreneurship and their contextual factors. This study uses survey data of Northern California wineries collected in 1999 and 2015 to understand the industry-specific dynamics of entrepreneurship. Data was gathered relating to winery operational environments, business characteristics and the perceived concerned contextual factors. It was hypothesized that the age and size of wineries will vary by perceived environmental factors and entrepreneurial thinking. Counter-intuitively it was found that larger and older wineries being more focused on entrepreneurial thinking than smaller and younger 'entrepreneurial' firms. It was also found that the concerns of industry contextual factors are shared by all industry players regardless of age, size and strategy. The practical findings provide wine industry participants with insights into the priorities for development of strategies, regardless of size and age.